(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research delves into the poetic works of Kamala das, a prominent poet, with a specificfocus on the depiction of feminine archetypes. The study centres on the themes of empowerment andsubversion as portrayed through these archetypal representations. By meticulously analyzing Kamala das’poetry, the study aims to illuminate how she crafts and employs various feminine archetypes to challengeconventional gender roles and societal norms. There is a sexual ’impropriety to her character’, whichscarcely covers her inward fervor. Qualified as the greater part legitimate and steady infamous writer,Kamala Das gets notoriety as the impact of women’s sexuality. There is a self-portraying vein in themajority of the sonnets of Kamala Das; she has likewise private an element style of her own. Her poetryis covered with a multi-layered model of feeling and standpoints. They describe to moving require. Wantand cruel is insight of aggravation and disappointment, lack and partition. Through a comprehensiveexploration of her poetic narratives, the research intends to contribute significantly to thecomprehension of Kamala das’ artistic approach in harnessing poetic expression for the dual purpose ofempowering women and subverting established gender paradigms. The study, by deciphering thetransformative potential of poetry, underscores the efficacy of literature in shaping new dimensions offemininity.